Cultural Diplomacy Through the Pacu Jalur Festival: Strengthening Riau’s Cultural Identity on the International Arena - Yuliyanti Talita Br. Purba; Triesanto Romulo Simanjuntak; Tunjung Wijanarka (International Journal of Social Sciences and Humanities, 2026)
This study aims to identify and analyze the role of cultural diplomacy through the Pacu Jalur Festival as an effort to strengthen Riau’s cultural identity at the international level. A descriptive qualitative method was employed, with the Pacu Jalur Festival serving as the primary unit of analysis within the framework of international relations. Data collection was conducted through in-depth interviews and a literature review based on official documents and previous research. The research findings indicate that the Pacu Jalur tradition has transformed from a 17th-century river transportation means into an international tourism festival included in the Karisma Event Nusantara (KEN). This festival has proven effective as a medium for international communication, an instrument for building a positive image, and a space for direct people-to-people interaction. The active involvement of local governments alongside the private sector through the digitalization of promotions has successfully triggered a surge in international tourist visits. Despite the event’s seasonal nature, Pacu Jalur has strengthened soft power and the presence of Malay culture on the global stage.